Akurasi Penerjemahan: Analisis Sinonim Kata Asal “Moderate” Hasil Terjemah Situs https://corpus.quran.com/ - Nursida, Ida; Yulyani, Rani Dewi; Raharja, Hatta (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2024)
The discussion on synonymy in language has been a topic of debate for centuries, with conflicting views on the existence of synonyms. This study aims to analyze the meaning of the word